2007
DOI: 10.1111/j.1467-8489.2007.00392.x
|View full text |Cite
|
Sign up to set email alerts
|

Productivity growth and the returns from public investment in R&D in Australian broadacre agriculture

Abstract: Investment in R&D has long been regarded as an important source of productivity growth in Australian agriculture. Perhaps because research lags are long, current investment in R&D is monitored closely. Investment in R&D has been flat while productivity growth has remained strong, relative both to other sectors of the Australian economy and to the agricultural sectors of other countries. Such productivity growth, at a time when the decline in terms of trade facing Australian farmers has slowed, may have enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 17 publications
2
47
0
Order By: Relevance
“…Here we confine our attention to the most recent analyses in both countries, those by Mullen (2007) and by Hall and Scobie (2006). The theory and methodology for estimating the link between research and MFP are reviewed in these papers and in Alston, Norton and Pardey (1995).…”
Section: 1mentioning
confidence: 96%
See 4 more Smart Citations
“…Here we confine our attention to the most recent analyses in both countries, those by Mullen (2007) and by Hall and Scobie (2006). The theory and methodology for estimating the link between research and MFP are reviewed in these papers and in Alston, Norton and Pardey (1995).…”
Section: 1mentioning
confidence: 96%
“…The growth in MFP over the whole period was 2.5%. Mullen (2007) concluded that while the Australian Bureau of Statistics (ABS) estimates of MFP at a sector level suggest some slowdown in growth in recent years and ABARE estimates suggest that productivity growth has slowed for specialist croppers, the evidence of a slowdown for broadacre agriculture generally is not yet strong especially given the run of poor seasons since 2000.…”
Section: 2mentioning
confidence: 97%
See 3 more Smart Citations